Health care for people with disabilities in a rural setting under the perspective of community agents - Daiane Zeni; Marta Cocco da Costa; Ethel Bastos da Silva; Fernanda Honnef; Jaqueline Arboit; Isabel Cristina dos Santos Colomé
ABSTRACT Objective: To understand how health care for people with disabilities in rural settings occurs according to the perspective of Community Health Agents. Methods: Qualitative approach study in which 13 Community Health Agents participated. Data collection took place through semi-structured interviews. The data were systematized and analyzed by Minayo's content analysis. Results: Some weaknesses and barriers make people with disabilities living in rural settings, invisible and distant from comprehensive and equitable health care. The weaknesses are related to unprepared CHAs and the inefficient qualifications to serve this population. The barriers to seeking comprehensive care are particularly physical, economic, geographical, and infrastructural. Final Considerations: It is imperative to give visibility to people with disabilities in the rural context, considering the singularities of this place, in order to enhance sensitive and welcoming care provided by health services.